Technical and Technological Conditions of Introducing Controlled Piggyback Transport Zagreb- West Europe - Pave Marinović; Grgo Luburić; Slavko Suk (Promet - Traffic&Transportation, 1970)
The development of combined transport is highly requiredby the European countries. The pressure, both administrativeand economic, is growing continuously for the use of railway asthe ecologically most suitable land carrier. Considering the protectionof roads, ecological, political and other reasons,Croatia will have to define her policy toward the 'Piggyback'transport in transit (mainly through conidors X and Vb). No efficientintegration into the European system of combined transportcan be expected without the necessa1y stimulating measuresby the government and without a clearly defined transportpolicy.